Variation of Biophysical Parameters of the Skin with Age, Gender, and Body Region - Alireza Firooz; Bardia Sadr; Shahab Babakoohi; Maryam Sarraf-Yazdy; Ferial Fanian; Ali Kazerouni-Timsar; Mansour Nassiri-Kashani; Mohammad Mehdi Naghizadeh; Yahya Dowlati (The Scientific World Journal)
Background. Understanding the physiological, chemical, and biophysical characteristics of the skin helps us to arrange a proper approach to the management of skin diseases. Objective. The aim of this study was to measure 6 biophysical characteristics of normal skin (sebum content, hydration, transepidermal water loss (TEWL), erythema index, melanin index, and elasticity) in a normal population and assess the effect of sex, age, and body location on them. Methods. Fifty healthy volunteers in 5 age groups (5 males and females in each) were enrolled in this study. A multifunctional skin physiology monitor (Courage & Khazaka electronic GmbH, Germany) was used to measure skin sebum content, hydration, TEWL, erythema index, melanin index, and elasticity in 8 different locations of the body. Results. There were significant differences between the hydration, melanin index, and elasticity of different age groups. Regarding the locations, forehead had the highest melanin index, where as palm had the lowest value. The mean values of erythema index and melanin index and TEWL were significantly higher in males and anatomic location was a significant independent factor for all of 6 measured parameters. Conclusion. Several biophysical properties of the skin vary among different gender, age groups, and body locations.